2003 USAMO Problems/Problem 5

Problem

Let $a$, $b$, $c$ be positive real numbers. Prove that

$\dfrac{(2a + b + c)^2}{2a^2 + (b + c)^2} + \dfrac{(2b + c + a)^2}{2b^2 + (c + a)^2} + \dfrac{(2c + a + b)^2}{2c^2 + (a + b)^2} \le 8.$

Solution

Solution 1

Since all terms are homogeneous, we may assume WLOG that $a + b + c = 3$.

Then the LHS becomes $\sum \frac {(a + 3)^2}{2a^2 + (3 - a)^2} = \sum \frac {a^2 + 6a + 9}{3a^2 - 6a + 9} = \sum \left(\frac {1}{3} + \frac {8a + 6}{3a^2 - 6a + 9}\right)$.

Notice $3a^2 - 6a + 9 = 3(a - 1)^2 + 6 \ge 6$, so $\frac {8a + 6}{3a^2 - 6a + 9} \le \frac {8a + 6}{6}$.

So $\sum \frac {(a + 3)^2}{2a^2 + (3 - a)^2} \le \sum \left(\frac {1}{3} + \frac {8a + 6}{6}\right) = 1 + \frac {8(a + b + c) + 18}{6} = 8$, as desired.

Solution 2

Note that \begin{align*} (2x + y)^2 + 2(x - y)^2 &= 4x^2 + 4xy + y^2 + 2x^2 - 4xy + 2y^2 \\ &= 3(2x^2 + y^2). \end{align*} Setting $x = a$ and $y = b + c$ yields \[(2a + b + c)^2 + 2(a - b - c)^2 = 3(2a^2 + (b + c)^2).\] Thus, we have

\[\frac{(2a + b + c)^2}{2a^2 + (b + c)^2 = \frac{3(2a^2 + (b + c)^2) - 2(a - b - c)^2}{2a^2 + (b + c)^2} = 3 - \frac{2(a - b - c)^2}{2a^2 + (b + c)^2},\] (Error compiling LaTeX. ! File ended while scanning use of \frac .)

and its analogous forms. Thus, the desired inequality is equivalent to \[\frac{(a - b - c)^2}{2a^2 + (b + c)^2} + \frac{(b - c - a)^2}{2b^2 + (c + a)^2} + \frac{(c - a - b)^2}{2c^2 + (a + b)^2}\geq\frac{1}{2}.\] Because $(b + c)^2\leq 2(b^2 + c^2)$, we have $2a^2 + (b + c)^2\leq 2(a^2 + b^2 + c^2)$ and its analogous forms. It suffices to show that \[\frac{(a - b - c)^2}{2(a^2 + b^2 + c^2)} + \frac{(b - c - a)^2}{2(a^2 + b^2 + c^2)} + \frac{(c - a - b)^2}{2(a^2 + b^2 + c^2)}\geq\frac{1}{2},\] or, \[(a - b - c)^2 + (b - a - c)^2 + (c - a - b)^2\geq a^2 + b^2 + c^2.\qquad\qquad (*)\] Multiplying this out the left-hand side of the last inequality gives $3(a^2 + b^2 + c^2) - 2(ab + bc + ca)$. Therefore the inequality $(*)$ is equivalent to $2[a^2 + b^2 + c^2 - (ab + bc + ca)]\geq 0$, which is evident because \[2[a^2 + b^2 + c^2 - (ab + bc + ca)] = (a - b)^2 + (b - c)^2 + (c - a)^2.\] Equality holds when $a = b = c$.

Solution 3

Given a function $f$ of three variables, define the cyclic sum \[\sum_{\text{cyc}}f(p,q,r) = f(p,q,r) + f(q,r,p) + f(r,p,q).\] We first convert the inequality into \[\sum_{\text{cyc}}\frac{2a(a + 2b + 2c)}{2a^2 + (b + c)^2}\leq 5.\] Splitting the 5 among the three terms yields the equivalent form \[\sum_{\text{cyc}}\frac{4a^2 - 12a(b + c) + 5(b + c)^2}{3[2a^2 + (b + c)^2]}\geq 0.\qquad\qquad (2)\] The numerator of the term shown factors as $(2a - x)(2a - 5x)$, where $x = b + c$. We will show that \[\frac{(2a - x)(2a - 5x)}{3(2a^2 + x^2)}\geq -\frac{4(2a - x)}{3(a + x)}.\qquad\qquad (3)\] Indeed, $(3)$ is equivalent to \[(2a - x)[(2a - 5x)(a + x) + 4(2a^2 + x^2)]\geq 0,\] which reduces to \[(2a - x)(10a^2 - 3ax - x^2) = (2a - x)^2(5a + x)\geq 0,\] evident. We proved that \[\frac{4a^2 - 12a(b + c) + 5(b + c)^2}{3[2a^2 + (b + c)^2]}\geq -\frac{4(2a - b - c)}{3(a + b + c)},\] hence $(2)$ follows. Equality holds if and only if $2a = b + c, 2b = c + a, 2c = a + b$, i.e., when $a = b = c$.

Solution 4

Given a function $f$ of $n$ variables, we define the symmetric sum \[\sum_{\text{sym}}f(x_1, \ldots, x_n) = \sum_{\sigma} f(x_{\sigma(1)}, \ldots, x_{\sigma(n)})\] where $\sigma$ runs over all permutations of $1, \ldots, n$ (for a total of $n!$ terms).

We combine the terms in the desired inequality over a common denominator and use symmetric sum notation to simplify the algebra. The numerator of the difference between the two sides is \[\sum_{\text{sym}} 8a^6 + 8a^5 + 2a^4b^2 + 10a^4bc + 10a^3b^3 - 52a^3b^2c + 14a^2b^2c^2.\] Recalling Schur's Inequality, we have \[a^3 + b^3 + c^3 + 3abc - (a^2b + b^2c + c^2a + ab^2 + bc^2 + ca^2) \\ = a(a - b)(a - c) + b(b - a)(b - c) + c(c - a)(c - b)\geq 0,\] or \[\sum_{\text{sym}} a^3 - 2a^2b + abc\geq 0.\] Hence, \[0\leq 14abc\sum_{\text{sym}} a^3 - 2a^2b + abc = \sum_{\text{sym}} 14a^4bc - 28a^3b^2c + 14a^2b^2c^2\] and by repeated AM-GM inequality, \[0\leq\sum_{\text{sym}} 4a^6 - 4a^4bc\] and \[0\leq\sum_{\text{sym}} 4a^6 + 8a^5b + 2a^4b^2 + 10a^3b^3 - 24a^3b^2c.\] Adding these three inequalities yields the desired result.

Alternate solutions are always welcome. If you have a different, elegant solution to this problem, please add it to this page.

See also

2003 USAMO (ProblemsResources)
Preceded by
Problem 4
Followed by
Problem 6
1 2 3 4 5 6
All USAMO Problems and Solutions
AMC logo.png
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.
ACS WASC
ACCREDITED
SCHOOL

Stay Connected

Subscribe to get news and
updates from AoPS, or Contact Us.
© 2015
AoPS Incorporated
Invalid username
Login to AoPS